A Systematic Review of the Effect of Self-Hypnosis on Quality of Life in Breast Cancer Patients - Padoli Padoli; Nur Hasanah; Nur Aini Luthfi Rahmawati (International Journal of Advanced Health Science and Technology, 2024)
Cancer is a chronic disease that affects the patient's quality of life. An important cause of cancer is emotional stress, anxiety and depression and emotional stress is known to persist after cancer treatment. This systematic review is aimed to determine the effect of hypnosis on the quality of life in breast cancer patients. Methods: A literature search was performed on databased from PubMed, SAGE, Scopus, ScienceDirect, EBSCOhost, in order to identified articles published from 2017 to 2022. The keywords to search those journals were “hypnosis” OR “self-hypnosis” AND “breast cancer” OR “Breast carcinoma” AND “quality of life” OR “wellbeing”. The detailed PICOT (Population, Intervention, Comparison, Outcome, Times) framework, established a priori, was used to include and exclude articles for this systematic review. Results.The results of the search and assessment resulted in 44 articles and then data extraction was carried out on 15 articles. It was found that hypnotherapy during surgery, chemotherapy and radiotherapy improved cognitive function and reduced adverse effects on social and physical function and improved overall quality of life in breast cancer patients. We suggest the need for randomized clinical trials to be conducted with sufficient follow-up and statistical power to confirm these results